ANALISIS KEPUASAN PENGGUNA SATUSEHAT MOBILE BERDASARKAN DATA ULASAN DI GOOGLE PLAY STORE MENGGUNAKAN LOGISTIC REGRESSION - Pratama, Febry (Journal of Advanced Research in Informatics, 2025)
Abstract - SATUSEHAT Mobile is a digital health service application developed by the Indonesian Ministry of Health as a continuation of the PeduliLindungi application. It is designed to provide more comprehensive healthcare services in the post-COVID-19 era. This study aims to analyze user satisfaction with the SATUSEHAT Mobile application based on user reviews collected from the Google Play Store. The methodology involves web scraping of review data using Python, data processing using Orange as a visual analytics platform, and the application of Text Mining and Logistic Regression classification techniques to analyze user sentiment. Sentiments were categorized into three classes: positive, neutral, and negative, based on the ratings given by users. The analysis results show that the majority of the reviews expressed positive sentiment, followed by neutral, with only a small portion being negative. These findings provide insights into public perception of the SATUSEHAT Mobile application and can serve as valuable input for developers to enhance the application's service quality and improve overall user satisfaction.